Terra prometida: igreja católica, agricultores sem-terra e o Serviço Nacional de Informações no norte do Rio Grande do Sul - Bonavigo, Mateus Manfrin (2024)
The research aims to analyze the military surveillance process reported by the National Information Service (SNI) on peasant mobilizations in defense of agrarian reform, which took place in the north of Rio Grande do Sul, between 1978-1993. The peasant organization defended the thesis that there was a lot of unproductive land in the region, which would allow the distribution of small properties to landless farmers, without the need to migrate to other states. From the beginning, a military surveillance apparatus was present over the movement, with emphasis on the figure of Colonel Sebastião Rodrigues de Moura (Curió), responsible for the attempts to dismantle the mobilizations. The support of the Catholic clergy for the movement's demands occurred from the beginning, gaining greater visibility in 1982, when the V Pilgrimage of the Land was held, at Encruzilhada Natalino, which profoundly marked the presence of the Church among the campers. In fact, the act marked the transfer of the camp to an area acquired by the Church, in the same municipality, a place where farmers organized themselves and fought for definitive settlements, a large part of which was covered in 1983. Since not all landless farmers Having received land, the remainder, on October 29, 1985, occupied the Annoni Farm, an unproductive area with more than 9,000 hectares, close to Encruzilhada Natalino. The pressure resulted in, from 1987 onwards, the area being divided up for the settlement of these families, obtaining definitive expropriation in 1993. In this process, landless farmers camp on the side of the road in Ronda Alta, in an attempt to be resettled by the State. . In September 1979, these farmers were settled on the Macali and Brilhante farms in Ronda Alta, but these lands were not enough to serve everyone, generating the camp at Encruzilhada Natalino, in 1985, and the occupation of the Annoni Farm, a major milestone in the reform agrarian. The tensions present in this scenario of dispute over land, in which different social actors expressed themselves, were carefully monitored by the government information and surveillance apparatus and by strong military intervention. The documentary sources that support the research refer mainly to the reports generated by the SNI during this process, which allowed us to delve into the complex relationship between the mobilization of landless people, the actions of the clergy and repressive operations.